Increased risk of severe vaso-occlusive episodes after initial acute chest syndrome in children with sickle cell anemia less than 4 years old: Sleep and Asthma Cohort - Vance, Leah D (Am J Hematol, 2015)
Previous studies have shown that the highest incidence of acute chest syndrome (ACS) in sickle cell disease (SCD) occurs in children less than 4 years old, and a history of ACS at this age is a risk factor for future ACS episodes. However, the interval associated with the highest risk of subsequent ACS or severe pain is not known. Through this mixed retrospective-prospective observational study, the Sleep and Asthma Cohort, we sought to determine the interval after an initial ACS episode during which the majority of children <4 years old are re-hospitalized for ACS or severe pain. The cumulative prevalence of re-hospitalization for ACS or severe pain within 6 months, 1 years, and 2 years was calculated for children with an initial ACS episode <4 years old and compared to children with an initial ACS episode ≥4 years old. A total of 44.8% and 55.2% of participants had an initial ACS episode <4 years and ≥4 years old (Range: 4-17.7 years), respectively. At 1 year following the initial ACS episode, children <4 years old had a significantly higher cumulative prevalence of re-hospitalizations for ACS or pain as compared to children ≥4 years of age, 62.5% and 39.1%, respectively (P = 0.009). After initial ACS episodes, the majority of children <4 years old will be re-hospitalized for ACS or severe pain within one year, suggesting the need for a therapeutic intervention for this high-risk group.